Biped Robots With Compliant Joints for Walking and Running Performance Growing - Maiorino, Andrea; Muscolo, Giovanni Gerardo (Frontiers in Mechanical Engineering, 2020)
This paper deals with the problem of compliance in biped robots locomotion. After a first literature review, we designed and simulated a 3D virtual model of a biped robot conceived with the same link dimensions (and weights) of a standard man. In all simulation, the same input to the robot actuators is proposed, modifying only the compliance. We first validated the model and then compared results increasing and reducing compliance on hip, knee and ankle joints. The very good results underline how the robot performances may be increased including the compliant element in the knee. In particular, we noted how including a proper value of the compliance in the knee, power and torque of the actuators may be reduced increasing robot speed.